Paleoenvironmental framework of dinosaur tracksites and other ichnofossils in Early Cretaceous mixed siliciclastic-carbonate deposits in the Neuquén Basin, northern Patagonia (Argentina) - Pazos, Pablo Jose (2012)
The study of the uppermost section of the Early Cretaceous Agrio Formation in northern Patagonia (Neuquén Basin) where dinosaur tracks assigned to cf. Therangospodus pandemicus are exposed (tracksites I and II) evidence mixed marginal marine siliciclastic-carbonate deposits. The succession was divided in two intervals. A lower one containing theropod tracks, recorded on top of subtidal oolithic limestones with tiny wave ripples suggesting shoreline fluctuations and subaerial exposure. Tidal influence is recognised by fining upward and prograding cycles starting with subtidal carbonates and ending with fine-grained siliciclastic deposits at the top, or rarely laminites. Dolomitization affects subtidal deposits generated in an alkaline media stressful for tracemakers.Intertidal facies include abundant heterolithic deposits, coquinas composed of gastropods encrusted by multilayered bryozoans and muddy levels with incipient mud cracking. Invertebrate ichnofossils recognized from tidally dominated deposits include Arenicolites, Kouphichnium, and Rhizocorallium. The upper interval is a transgressive?regressive cycle that starts with dark shales, deficiently oxygenated, and covered by prograding sandstones and finally sand flat deposits. This interval contains Gyrochorte, Hillichnus, and Ophiomorpha documented in wave-influenced sandstones. Dinosaur tracks as well as Hillichnus, attributed to tellinoid bivalves, and Kouphichnium assigned to xiphosurans, imply the activity of producers rarely recorded previously as body fossils in marginal marine deposits of southern South America. Previous paleogeographic schemes are questioned by our analysis, which shows evidence of extremely shallow and tide-controlled sedimentation, sometimes with subaerial exposure, with high cyclicity related to a marginal marine depositional setting and lack of significant erosion by the overlying unit, as traditionally was suggested.